Cardiovascular Risk Factors and Hemodynamic Measures as Determinants of Increased Arterial Stiffness Following Surgical Aortic Valve Replacement - Plunde, Oscar; Franco-Cereceda, Anders; Bäck, Magnus (Frontiers in Cardiovascular Medicine, 2021)
Valvular and arterial function are tightly intertwined, both in terms of structural changes and hemodynamics. While proximal valvulo-vascular coupling contributes to the cardiovascular consequences of aortic stenosis, less is known on how peripheral arterial stiffness relates to aortic valve disease. Previous studies have shown conflicting results regarding the impact of aortic valve replacement on arterial stiffness. The aim of the present study was therefore to determine predictors of arterial stiffness in patients with and without aortic valve disease undergoing cardiac surgery. Cardio ankle vascular index (CAVI) and carotid femoral pulse wave velocity (cfPWV) were measured to determine arterial stiffness the day before and 3 days after surgery for either ascending aortic or aortic valve disease. Stratification on indication for surgery revealed that CAVI was significantly lower in patients with aortic valve stenosis (n=45) and aortic valve regurgitation (n=30) compared with those with isolated ascending aortic dilatation (n=13). After surgery, a significant increased CAVI was observed in aortic stenosis (median 1.34, IQR 0.74 - 2.26, p<0.001) and regurgitation (median 1.04, IQR 0.01 - 1.49, p=0.003) patients while cfPWV was not significantly changed. Age, diabetes, low body mass index, low preoperative CAVI, as well as changes in ejection time were independently associated with increased CAVI after surgery. The results of the present study suggest aortic valve disease as cause of underestimation of arterial stiffness when including peripheral segments. We report cardiovascular risk factors and pinpoint the hemodynamic aspect ejection time to be associated with increased CAVI after aortic valve surgery.